1980
DOI: 10.1093/infdis/141.6.702
|View full text |Cite
|
Sign up to set email alerts
|

Disease Due to Enterotoxigenic Escherichia coli in Bangladeshi Adults: Clinical Aspects and a Controlled Trial of Tetracycline

Abstract: The clinical characteristics of disease due to enterotoxigenic Escherichia coli (ETEC) were determined in 88 adult males admitted to a hospital in Dacca, Bangladesh, with moderate to severe dehydration. Persons infected with ETEC strains producing both heat-labile toxin (LT) and heat-stable (ST) toxin had more dehydration and acidosis, longer duration of illness, and greater stool volume than persons infected with strains producing only ST. Tetracycline therapy, evaluated in 63 cases, resulted in slightly earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2

Year Published

1983
1983
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 21 publications
2
17
2
Order By: Relevance
“…These findings from Calcutta were soon confirmed by oral challenge of human volunteers (49,100) and by corroboration of studies in Dhaka, Bangladesh (61,113,117,149). ETEC were shown in these studies to be most frequently found in children; such findings have been subsequently corroborated in multiple studies in developing countries (23,24).…”
Section: Historical Aspects From Discovery To Present Understanding Omentioning
confidence: 55%
See 3 more Smart Citations
“…These findings from Calcutta were soon confirmed by oral challenge of human volunteers (49,100) and by corroboration of studies in Dhaka, Bangladesh (61,113,117,149). ETEC were shown in these studies to be most frequently found in children; such findings have been subsequently corroborated in multiple studies in developing countries (23,24).…”
Section: Historical Aspects From Discovery To Present Understanding Omentioning
confidence: 55%
“…The incidence of ETEC infections in developing countries decreases after 5 years of age with a decrease of infections between the ages of 5 to 15 years (Table 6). The incidence increases again in those over 15 years of age and about 25% of ETEC illness is seen in adults (113,132). Limited epidemiological information is available for adults, and those available are mostly from India and Bangladesh.…”
Section: Age-related Infections In Children and Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enterotoxigenic Escherichia coli (ETEC) have been reported to be a major cause of diarrhoea in man throughout the world (Sack, 1975;Rowe et al, 1977), notably in developing countries (Merson et al, 1980). They have also been found to be the commonest cause of travellers' diarrhoea in all countries where surveys have been conducted (Merson et al, 1976;Echeverria et al, 1981 ;Ryder et al, 1981).…”
Section: Introductionmentioning
confidence: 99%